The geometry of the ICRF-induced wave–SOL interaction. A multi-machine experimental review in view of the ITER operation. (13th December 2021) - Colas, L.; Urbanczyk, G.; Goniche, M.; Hillairet, J.; Bernard, J.-M.; Bourdelle, C.; Fedorczak, N.; Guillemaut, C.; Helou, W.; Bobkov, V.; Ochoukov, R.; Jacquet, Ph.; et al.
Abstract: As part of ITPA-Integrated Operational Scenario activities, this contribution reviews recent experimental characterizations of radio-frequency (RF)-induced scrape-off layer (SOL) modifications of various tokamaks worldwide and of the LArge Plasma Device at UCLA. The phenomenology, as observed using a large variety of measurement techniques, is consistent with expectations from RF sheath rectification. Emphasis is then put on the complex three-dimensional (3D) spatial patterns of the RF–SOL interaction, in relation to the magnetic topology and the spatial distribution of RF currents over the metallic structures surrounding the RF wave launchers. Dependence on the local plasma parameters in the antenna vicinity is also briefly addressed. The final part discusses implications for future devices.